Faktor-Faktor Penghambat Penyidikan terhadap Tindak Pidana Perdagangan Orang (Human Trafficking) di Polres Timor Tengah Selatan - Emma Frederika Lakapu; Renny Rebeka Masu; A. Resopijani (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This study aims to find out and analyze the factors that hinder the investigation of human trafficking in South Central Timor. This research is an empirical legal research supported by a qualitative approach using primary data in the form of interviews and secondary data in the form of information, literature studies, literature books, documents, laws and regulations, and other written sources related to research collected using interview techniques, literature studies and documentation studies that are analyzed in a qualitative descriptive manner. The results of the study show that (1) Police Actions in the Eradication of Trafficking in Persons by the South Central Timor Resort Police include, Pre-emptive Actions and Preventive Measures and Repressive Actions. (2) Efforts Made to Overcome Obstacles in the Investigation Process for the Crime of Trafficking in Persons, namely the first effort, carried out persuasively, the second effort, the police make efforts by convincing using words and the third effort, the police give advice to the victim's parents to keep their children, especially their daughters, more strictly, (3) The role of the Manpower and Transmigration Office of South Central Timor Regency in Handling the Crime of Trafficking in Persons and the Role of Local Governments in Supporting the Overcoming of Persons is to increase public understanding of the procedures and mechanisms for working out, both between regions and between countries.